Primary Productivity of Phytoplankton in The Mandalika Coastal Waters Special Economic Zone, Central Lombok Regency - Fidyantini, Findi; Candri, Dining Aidil; Japa, Lalu; Ghazali, Mursal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The research entitled